Clinico-morphological Profile of Cutaneous Fungal Infections: An Experience from a Tertiary Care Government Hospital in North India - Jain, Ekta; Punia, Rajpal Singh; Chander, Jagdish; Bhalla, Mala (Annals of Pathology and Laboratory Medicine, 2021)
Background: Cutaneous fungal infections are predominantly seen in hot tropical countries like India. In the past decade, there has been an escalation in recurrent and chronic fungal infections. Skin biopsy may play a critical role in rapid identification of these infections. Methods: Fifteen cases of cutaneous fungal infections over a period of 6 years were included. Formalin-fixed tissue was subjected to hematoxylin and eosin and histochemical staining including Gomori Methanamine Silver and Periodic Acid Schiff . Results of KOH smear test and fungal culture were included wherever available. The clinico-morphological patterns in various cutaneous fungal infections was evaluated. Results: Most patients were between 25 to 40 years of age and commonly presented as skin ulceration, followed by nodular swelling and multiple discharging sinuses. Candidiasis and Mycetoma infections were the commonest infections. Others included: Cryptococcosis, Dermatophytosis, Chromoblastomycosis and Mucormycosis. The predominant histopathologic patterns were perivascular and interstitial inflammation. Eleven cases were confirmed by KOH examination and culture. Conclusion: The morphologic spectrum of cutaneous fungal infections is varied. Initial presentations of these fungal infections may be indicative of the onset of a life-threatening systemic mycoses. Thus, the histopathologic evaluation of skin tissue specimens is critical for their rapid and accurate diagnosis.